Optimization strategies and artifacts of time‐involved small‐angle neutron scattering experiments. Issue 6 (29th November 2022) - Mettus, Denis; Chacon, Alfonso; Bauer, Andreas; Mühlbauer, Sebastian; Pfleiderer, Christian
Abstract : This article reviews the opportunities and limitations of time‐involved small‐angle neutron scattering experiments, with the typical artifacts of the recorded data illustrated by virtue of the response of the skyrmion lattice in MnSi under periodic changes of the direction of the stabilizing field. Abstract : Kinetic small‐angle neutron scattering provides access to the microscopic properties of mesoscale systems under slow, periodic perturbations. By interlocking the phases of neutron pulse, sample modulation and detector signal, time‐involved small‐angle neutron scattering experiments (TISANE) allow one to exploit the neutron velocity spread and record data without major sacrifice in intensity at timescales down to microseconds. This article reviews the optimization strategies of TISANE that arise from specific aspects of the process of data acquisition and data analysis starting from the basic principles of operation. Typical artifacts of data recorded in TISANE due to the choice of time binning and neutron chopper pulse width are illustrated by virtue of the response of the skyrmion lattice in MnSi under periodic changes of the direction of the stabilizing magnetic field.